Pathways into homelessness: Understanding how both individual and structural factors contribute to and sustain homelessness in Canada. (October 2015) - Piat, Myra; Polvere, Lauren; Kirst, Maritt; Voronka, Jijian; Zabkiewicz, Denise; Plante, Marie-Carmen; Isaak, Corinne; Nolin, Danielle; Nelson, Geoffrey; Goering, Paula
This qualitative study examined how homeless individuals with mental illness experience pathways into homelessness. Study participants were enrolled in the At Home/Chez Soi project, a Pan-Canadian Randomized Controlled Trial comparing the Housing First approach with Treatment as Usual for homeless individuals. This inquiry is grounded in social ecological perspective, which considers interactions between individual and structural factors. Findings from consumer narrative interviews ( n  = 219) revealed that individual factors, such as substance abuse, relationship conflicts and mental health issues significantly contributed to homelessness, in addition to structural transitions from foster care and institutional settings into the community. Additional structural factors entrenched participants in unsafe communities, created obstacles to exiting homelessness and amplified individual risk factors. The study findings confirm the role of individual risk factors in pathways into homelessness, but underscore the need for policies and interventions to address structural factors that worsen individual risks and create barriers to exiting homelessness.